Diagnostic value of gadobutrol versus gadopentetate dimeglumine in enhanced MRI of brain metastases. Issue 6 (3rd October 2016) - Fan, Bing; Li, Meijiao; Wang, Xiaoying; Xu, Yufeng; Li, Feiyu; Zhang, Laiyun; Jiang, Jian; Jiang, Yanyan
Abstract : Purpose: To compare gadobutrol and gadopentetate dimeglumine (Gd‐DTPA) contrast‐enhanced magnetic resonance imaging (MRI) at 3T for visualizing brain metastases. Materials and Methods: The present randomized study included 60 consecutive patients with known or suspected brain metastases from systemic malignancies. Two enhanced cerebral MR scans were performed in each patient within an interval of 2–5 days using different contrast agents (gadobutrol or Gd‐DTPA) at 3T. The dose of the contrast agents (0.1 mmol/kg Gd) was also identical. The axial T 1 FLAIR images at 3, 7, and 10 minutes after the injection of the contrast agent were obtained for evaluation. Two experienced radiologists performed subjective evaluation of the image quality, made the choice of the optimal images, and performed an objective evaluation including: signal‐to‐noise ratio (SNR) of the brain metastases, contrast‐to‐noise ratio (CNR), contrast enhancement (CE), contrast‐to‐brain ratio (CBR), and contrast enhancement ratio (CER) of the brain metastases. Results: Subjective evaluation showed that at 3, 7, and 10 minutes gadobutrol elicited higher scores (margin score: 3.56 ± 0.74 vs. 3.33 ± 0.93, 3.68 ± 0.57 vs. 3.45 ± 0.81, 3.58 ± 0.71 vs. 3.43 ± 0.76; interior score: 2.83 ± 0.42 vs. 2.63 ± 0.61, 2.86 ± 0.38 vs. 2.73 ± 0.52, 2.80 ± 0.42 vs. 2.69 ± 0.53; and overall score: 4.42 ± 0.98 vs. 4.09 ± 1.19, 4.57 ± 0.75 vs. 4.26 ± 1.05, 4.48 ± 0.83 vs. 4.21 ± 1.03, respectively) in displaying the details and overall lesions than Gd‐DTPA (repeated measures analysis of variance [ANOVA], margin score: P  = 0.001, < 0.0001, 0.006; interior score: P < 0.0001, 0.004, 0.009; and overall score: P  = 0.001, < 0.0001, < 0.0001, respectively). Subjective optimal image evaluation showed that the percentage of image assessed as "gadobutrol was better than Gd‐DTPA (41.2–44.1%)" was greater than that assessed as "Gd‐DTPA was better than gadobutrol (5.9–26.5%)." Objective evaluation showed that at 3, 7, and 10 minutes the SNR (214.17 ± 85.70 vs. 199.57 ± 85.08, 214.80 ± 86.03 vs. 199.19 ± 84.74, and 213.83 ± 82.46 vs. 193.68 ± 79.59, respectively), CNR (68.64 ± 50.18 vs. 57.88 ± 51.06, 75.42 ± 53.19 vs. 63.74 ± 53.91, and 77.13 ± 51.86 vs. 63.21 ± 51.71, respectively), CE (101.76 ± 63.31 vs. 87.61 ± 64.85, 99.85 ± 61.56 vs. 85.08 ± 64.98, and 100.33 ± 58.63 vs. 82.73 ± 61.73, respectively), CBR (0.48 ± 0.32 vs. 0.40 ± 0.33, 0.54 ± 0.34 vs. 0.46 ± 0.35, and 0.56 ± 0.34 vs. 0.47 ± 0.34, respectively), and CER (0.99 ± 0.69 vs. 0.88 ± 0.81, 0.97 ± 0.68 vs. 0.86 ± 0.84, and 0.98 ± 0.65 vs. 0.85 ± 0.80, respectively) were all higher when using gadobutrol compared with Gd‐DTPA in the enhanced MR (repeated measures ANOVA, all P < 0.0001). On Gd‐DTPA enhanced images, 289, 292, and 292 lesions at 3, 7, and 10 minutes were detected by the two radiologists, while 295, 301, and 301 lesions were detected on gadobutrol‐enhanced images, respectively. Conclusion: Using a 3T T 1 FLAIR sequence, gadobutrol (0.1 mmol/kg body weight)‐enhanced MR resulted in more conspicuous brain metastases, and more metastases compared with the same dose of Gd‐DTPA. A delay time of 7 minutes for postcontrast MRI in patients with brain metastases is suggested in clinical practice. Level of Evidence : 2 J. MAGN. RESON. IMAGING 2017;45:1827–1834